COW MILK PRODUCTION AND FARM STABILITY IN AGRARIAN REFORM SETTLEMENTS IN THE SOUTH-EASTERN AMAZON - Pereira, Taynã Zanderly da Silva; Martins, Paulo Fernando da Silva; Nogueira, Felipe Domingues; Rocha, Amália Gabriela Aguiar (REVISTA DE AGRICULTURA, 2019)
This article analyses the current situation and prospects of the permanence of farmers in cow mil production on their lots in two agrarian reform settlements with different historical contexts located in the Marabá municipality, Pará State, Brazil. The analysis makes statistical comparisons with single-factor ANOVA to compare strata between groups of farms that do and do not sell milk and Pearson’s correlation and simple linear regression analysis to evaluate differences among indicators of livestock husbandry activities to identify the best indicator variables for the improvement of productivity and milk sales. Milk production increases when financial credit is present; however, the sale of milk in agrarian reform farms is hampered by the low intensification of this activity and the need for more land to support the herd, which jeopardises the stability of farms and the permanence of family farmers on their lots end favours the migration to urban centres.